EVALUATION OF THE EFFECTIVENESS OF ORGANIZATIONAL AND DENTAL MEASURES FOR THE PREVENTION OF DENTAL PERIODONTAL DISEASES AMONG WORKERS IN THE PRODUCTION OF METAL STRUCTURES OF METAL PROCESSING ENTERPRISES - Madina A. Khatamova; Nodira Sh. Nazarova (Central Asian Journal of Medicine, 2024)
Periodontal is a complex multifunctional complex of tissues surrounding and retaining the tooth, interconnected morphologically, functionally and genetically, and includes the gum, periodontal, root cement and dental well (alveoli). Periodontal diseases are one of the urgent problems of dentistry. This group includes all pathological processes occurring in the periodontium. They can be of varying severity and develop independently or against the background of general somatic diseases. Pathological processes in the periodontium can be inflammatory or dystrophic in nature (a combination of them is often observed). Periodontal diseases lead to significant violations of the dental system, the development of purulent-inflammatory diseases of the maxillofacial region and in most cases to infectious sensitization, chronic intoxication and changes in the immune status of the body.